Behavioral and Physiological Interventions for Anxiety and Depression: An Overview of Nontraditional Methods. Issue 4 (2nd October 2019) - Oswald, Gina; Francis, Joshua; Dhakal, Sanjeev
ABSTRACT: Public health, social well-being, and human rights worldwide have all been impactd by the effects of anxiety and depression. The helping fields have spent over a century attempting to improve people's emotional well-being through traditional methods. However, there has been a recent explosion of holistic treatments that are growing in acceptance and evidenced-based support. This paper will provide a broad overview of several unconventional, alternative treatment interventions with growing evidence of their effectiveness as either a complementary or stand-alone treatment for anxiety and depression. Clinicians may learn about these emerging interventions in an effort to stay abreast of the most beneficial treatment models available and meet ethical guidelines.